2017
DOI: 10.4315/0362-028x.jfp-16-532
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Staphylococcal Enterotoxins in Ready-to-Eat Foods Sold in Istanbul

Abstract: The aim of this study was to investigate the prevalence of staphylococcal enterotoxins (SEs) in ready-to-eat (RTE) foods sold in Istanbul, Turkey. A total of 5,241 samples were randomly collected from various caterers, hotels, and restaurants from 2014 to 2016. The samples were classified into four groups: (i) various cooked RTE meat and vegetable meals, (ii) various RTE salads, charcuterie, and cold appetizers, (iii) various cooked RTE bakery products (pasta, pastries, pizza, pita, ravioli, etc.), and (iv) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…This clearly showed that there is a need to continue research to find certain natural agents to inhibit MDR S. aureus bacteria which exist in ready-to-eat foods. The most probable cause of high microbial count in beef processed meat might be the low hygienic quality of raw meat, insufficient storage, and thawing conditions, contamination from grinder, and the time between mincing and mixing [ 6 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…This clearly showed that there is a need to continue research to find certain natural agents to inhibit MDR S. aureus bacteria which exist in ready-to-eat foods. The most probable cause of high microbial count in beef processed meat might be the low hygienic quality of raw meat, insufficient storage, and thawing conditions, contamination from grinder, and the time between mincing and mixing [ 6 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…S. aureus es una de las especies más estudiadas y conocidas de su género, dado que se encuentra comúnmente en la piel y en las mucosas del ser humano. Y pese a que varias personas son portadoras asintomáticas, ello no exime su capacidad para ocasionar una amplia variedad de infecciones y enfermedades en el organismo: desde patologías leves en la piel hasta infecciones graves a nivel sanguíneo, óseo, cardiaco, respiratorio (neumonía), entre otras (Ulusoy et al, 2017;Hennekinne et al, 2012;Torres et al, 2021).…”
Section: Introductionunclassified
“…The increasing consumption of ready-to-eat (RTE) foods, in places other than the home, in recent years may pose a food safety problem if RTE foods are prepared improperly since they have suitable internal factors for the growth of spoilage, pathogenic and toxin-producing bacteria [7].…”
Section: Introductionmentioning
confidence: 99%